Antibacterial Activity of Commercial and Wild Cinnamon Species - Sharma3, Ashish Saraf1*, Mohit S Mishra2; K. (Journal of Phytology, 2011)
Butanolic extracts of two different Cinnamon species (C. zeylanicum; Commercial variety and C. flexuous; Wild variety), were investigated for their in vitro antibacterial activity. The antibacterial activity against plant and human pathogenic bacteria was evaluated on the basis of Inhibition Zones (IZs) measurement by Ã¢â‚¬Å“Disc diffusion methodÃ¢â‚¬Â. Maximum inhibition was shown by C. zeylanicum against gram positive bacterium-Staphylococcus aureus. C. flexuous extract also showed inhibition but was inactive against Klebsiella pneumoniae. C. flexuous extract was more active than C. flexuous as indicated by the results. The Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) valuesÃ‚Â for both the seeds (in ÃŽÂ¼g/ml) were also determined. The lowest value was obtained for Staphylococcus aureus [MIC-76.25 (C. f.) 78.5(C. z.)Ã‚Â MBC- 11 2.6(C. f.) 98.35(C. z.)] thus this bacteria is most inhibited by the extract, whereas Bacillus subtilis was least inhibited as indicated by MIC[( 98.50 (C. f.) 96.2 (C. z.)] and MBCÃ‚Â [169.50 (C. f.) 151.2 (C. z.)] values. Key words: Antibacterial, C. zeylanicum, C. flexuous, MIC, MBC <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Ashish Saraf et al. Antibacterial Activity of Commercial and Wild Cinnamon Species. J Phytol 3/2 (2011) 102-106.